(untitled) (Bulletin of Innovative Research, 2026)
This article discusses the stylistic features of Ahmad Yasawi’s Devoni Hikmat. It first interprets the folk-like simplicity, the Sufi thematic depth, and the closeness to oral speech characteristic of Yasawi’s wisdoms. It also notes that the artistic style of Devoni Hikmat initiated a new religious-spiritual direction in Turkic literature. The article analyzes the use of artistic imagery in the work, its resonance with the spirit of the people, and its educational significance.